Expert meeting on noncommunicable disease prevention and control: learning from the arts. World Health Organization (Who). Regional Office for Europe - Ávila Valdés, Noemi (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2023)
Many factors that affect our health and well-being are social, cultural, political, psychological or economic. Over the past two decades, there has been a major increase in research on the effect of the arts on health and well-being. Evidence indicates that art interventions can play a significant role in the prevention of ill health, promotion of health, and management and treatment of NCDs across the lifespan. Additionally, the arts can be an effective vehicle to deliver health messages; particularly for those who are the most difficult to reach. The WHO Regional Office for Europe is, therefore, convened an expert meeting to understand the state of play and the potential role of the arts in NCD prevention and treatment both within the Region and globally. The meeting enabled a multidisciplinary platform for sharing existing country experience and best practice case studies which have the potential to influence NCDs. It was explored this topic further through the lens of behavioural and cultural insights – a flagship initiative of the WHO European Programme of Work, 2020–2025. This meeting has been an opportunity to share and learn together (stakeholders from the arts, cultural institutions, health-care practitioners, academics, policy-makers and behavioural insight and digital health experts).